2016
DOI: 10.1177/1460458215569004
|View full text |Cite
|
Sign up to set email alerts
|

Electronic reporting of all reference laboratory results: An important step toward a truly all-encompassing, integrated health record

Abstract: Results from reference laboratories are often not easily available in electronic health records. This article describes a multi-pronged, long-term approach that includes bringing send-out tests in-house, upgrading the laboratory information system, interfacing more send-out tests and more reference laboratories, utilizing the "miscellaneous assay" option offered by some reference laboratories, and scanning all remaining paper reports from reference laboratories for display in the electronic health record. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The lack of motivation and prioritisation by professionals to enter data was identified as key barriers that need to be overcome. As observed by Kratz, 5 it is expected that more and more technologies and novel approaches will become available to minimise the need for manual data entry. O'Brien et al 6 proposed the redesign of the documentation process for nurses, where they concluded that one can expect that the value of nursing data will increase in the future and can represent a key differentiator for the economic success of the healthcare institutions by higher effectiveness and lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of motivation and prioritisation by professionals to enter data was identified as key barriers that need to be overcome. As observed by Kratz, 5 it is expected that more and more technologies and novel approaches will become available to minimise the need for manual data entry. O'Brien et al 6 proposed the redesign of the documentation process for nurses, where they concluded that one can expect that the value of nursing data will increase in the future and can represent a key differentiator for the economic success of the healthcare institutions by higher effectiveness and lower costs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings speak to the importance of developing systems to integrate PGx test results into the EHR as discrete data. Although the challenges of integrating reference laboratory test results into EHRs have been welldocumented [16], doing so would help to facilitate recall of pertinent test results at the point-of-prescribing [17,18]. Our findings highlight the urgency to develop better systems both for electronic integration of reference laboratory results and clinical decision support to facilitate appropriate use of PGx test results longitudinally.…”
Section: Discussionmentioning
confidence: 84%
“…Due to the complexity of the cases treated at our hospital, over 200,000 assays and panels are sent to over 60 di erent outside reference laboratories every year. [33] As of 2019, we worked with a structured database of 6.38 million patients that counts:…”
Section: Introductionmentioning
confidence: 99%